2010
DOI: 10.1007/s10681-010-0266-0
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of molecular markers linked to the eyespot resistance gene Pch1 in wheat

Abstract: Eyespot is a major disease of common wheat (Triticum aestivum L.) in temperate climates and causes yield losses of up to 40%. The causal agents of eyespot are Oculimacula acuformis (syn. Tapesia acuformis; anamorph: Helgardia acuformis syn. Pseudocercosporella herpotrichoides var. acuformis) and O. yallundae (syn. T. yallundae; anamorph: H. yallundae syn. P. h. var. herpotrichoides). Pch1 located on chromosome 7DL is the most important and most effective resistance gene, but its use in practical breeding is li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…AB246917 is 96 and 91 % similar to Traes_7DL_DBBA5FD6C and Bradi29400 , respectively, and encodes the endopeptidase protein Ep-D1b. A number of the previous studies detected a complete linkage between Pch1 and either the isozyme marker (McMillin et al 1986; Santra et al 2006) or the STS marker (Burt and Nicholson 2011; Leonard et al 2008; Meyer et al 2011). In accordance with these studies, our data also did not identify any recombination event between Xorw1_D and Pch1 , not making it possible to refute the hypothesis that Ep-D1b could be a candidate for Pch1 .…”
Section: Discussionmentioning
confidence: 98%
“…AB246917 is 96 and 91 % similar to Traes_7DL_DBBA5FD6C and Bradi29400 , respectively, and encodes the endopeptidase protein Ep-D1b. A number of the previous studies detected a complete linkage between Pch1 and either the isozyme marker (McMillin et al 1986; Santra et al 2006) or the STS marker (Burt and Nicholson 2011; Leonard et al 2008; Meyer et al 2011). In accordance with these studies, our data also did not identify any recombination event between Xorw1_D and Pch1 , not making it possible to refute the hypothesis that Ep-D1b could be a candidate for Pch1 .…”
Section: Discussionmentioning
confidence: 98%
“…Chapman et al (2008) also found that markers wmc14, barc97, and psr121 were closely linked with Pch1. Meyer et al (2011) reported that orw1, orw6, and cfd175 were the most suitable markers for marker assisted selection (MAS).…”
Section: Introductionmentioning
confidence: 99%
“…Disease is caused by two closely related fungal species Oculimacula yallundae and O. acuformis which infect wheat (Triticum aestivum L., Triticum durum L.), barley (Hordeum vulgare L.), oats (Avena sativa L.) and rye (Secale cereale L.). In cases of severe infection, the disease causes lodging and premature ripening of grain, leading to yield losses of up to 40% (Meyer et al 2011).…”
mentioning
confidence: 99%